Potential and real drug interactions in patients treated with abiraterone or enzalutamide in clinical practice. (2nd December 2021) - Vicente-Valor, Juan; Escudero-Vilaplana, Vicente; Collado-Borrell, Roberto; Pérez-Ramírez, Sara; Villanueva-Bueno, Cristina; Narrillos-Moraza, Álvaro; García-Sánchez, Sebastián; Beamud-Cortés, Manel; Herranz, Ana; Sanjurjo, María
ABSTRACT: Background: Abiraterone and enzalutamide, androgen receptor pathway inhibitors (ARPI) for the treatment of metastatic castration-resistant prostate cancer (mCRPC), are at high risk of potential drug interactions (PDIs). We aimed to describe PDIs and their management, and triggered adverse events (AEs) in clinical practice. Methods: We conducted a cross-sectional study in mCRPC patients who started treatment with abiraterone or enzalutamide in a university hospital between August 1st, 2016 and July 31st, 2020. Lexicomp® was used to identify and analyze PDIs, and the clinical records to assess their management and the occurrence of AEs. Results: We included 173 patients: 36.8% and 93.0% treated with abiraterone and enzalutamide, respectively, had at least 1 PDI. Globally, 6.3% of PDIs had X-risk (contraindication due to high probability of AE). Treatment was modified in 9.2% of patients and 9.8% suffered AEs due to PDIs. Factors associated with a higher risk of PDIs were polypharmacy (OR= 41.0, p 0.003) and treatment with enzalutamide (OR= 128.26, p < 0.001). Conclusions: At least two-thirds of patients treated with ARPI suffered a PDI. Overall, abiraterone would have a more favorable PDI profile. Knowing these interaction profiles may be helpful to develop a more efficient therapeutic follow-up and to select the safest treatment.